Additional femoral nerve block analgesia does not reduce the chronic pain after total knee arthroplasty: A retrospective study in patients with knee osteoarthritis. Issue 13 (March 2019) - Yao, Yuan-yuan; Zhou, Qing-he; Yu, Li-na; Yan, Min
Abstract : Abstract: Femoral nerve block analgesia was deemed to the gold standard for acute pain management after total knee arthroplasty (TKA). But effect on chronic pain management is not investigated fully. We conducted a retrospective study to explore the effect of single-injection femoral nerve block on postsurgical chronic pain. All medical records of patients undertaking TKA between January, 2013 and June, 2014 were reviewed via the Docare anesthesia database. Patients who administrated with the self-controlled intravenous analgesia were assigned to group P. Patients who received a single-injection femoral never block combined with patient self-controlled intravenous analgesia were assigned to group N + P. The visual analog scale (VAS) score before surgery, the first postoperative day (POD 1), POD 2, 3 months, 6 months, and 12 months after surgery were extracted from medical records. Pain score was compared over these 2 groups to investigate treatment outcomes. In all, 470 patients met the selection criteria for group P and 266 patients met the selection criteria for group N + P. Compared with group P, the VAS score decreased significantly in group N + P at POD 1 ( P  < .001), and the same was observed at POD 2 ( P  < .001); the moderate to severe pain incidence rate decreased significantly in group N + P at POD 1 ( P  < .01) and POD 2 (motion, P  < .001). The rescued anesthesia rate reduced significantly in group N + P in POD 1 ( P  = .001), whereas no difference was found in POD 2 ( P  = .864). No difference was found at 3, 6, and 12 months after surgery (all P  > .05). The single-injection femoral nerve block could relieve the acute postsurgical pain in a short period of time. But no evidence was found that it could reduce the chronic pain between 3 and 12 months after TKA.